Study on the performance of the new composite thermal insulation lining for the railway operational tunnel in cold regions. (August 2022) - Wang, Libin; Zhang, Chengping; Cui, Guangyao; Wang, Xuelai; Ye, Zijian
Abstract: In railway tunnels located in cold regions, frost damage is constantly emerging, which seriously affects the safety of railway tunnel operations. While having general thermal insulation effects, thermal insulation measures developed in previous studies have not solved the problem of frost damage in operational railway tunnels. To fill this gap, this paper puts forward a new composite thermal insulation lining. Firstly, through numerical simulation, this new composite thermal insulation lining was verified to have better mechanical properties and insulation effects than general steel plate thermal insulation lining. The fast construction method of thermal insulation lining is proposed to have excellent construction efficiency and great economic and social benefits. According to field monitoring data, the outer surface temperature of the lining reached about 5 °C in winter after the new composite thermal insulation lining was added, which fundamentally inhibited the formation of ice and effectively avoided frost damage. At the coldest moment in time, the temperature of the secondary lining was about 9 °C higher than without thermal insulation lining. In summary, compared with existing anti-freeze technology, the new composite thermal insulation lining has better thermal insulation capacity, can be constructed faster, and offers clear economic benefits. Highlights: A new thermal insulation lining for railway tunnel in cold regions is proposed. A fast construction method of thermal insulation lining is put forward. Insulation and mechanical properties are explored by numerical simulation and test.